Designing successful post-retirement solutions by blending growth, income and protection. (13th March 2017) - Morgan, L.-A.; Lothian, S. A.
Abstract: The move from defined benefit to defined contribution (DC) has transferred the longevity and investment risks from the plan sponsor to the individual plan member. Without the actuarial cross-subsidies implied by pooling these risks, the danger of outliving one's savings is significant. Much attention has been focussed on pre-retirement investment design but less on post-retirement. In most countries, the post-retirement systems in place are insufficient to solve this challenge for small asset sizes or small proportions of individuals' retirement accounts. However, a number of DC markets are mature, such as Australia and Chile, and the principles of a solution that works for all must be identified. This paper researches a number of post-retirement systems around the world and identifies ten key factors that contribute to post-retirement solution design. These factors can result in an inconsistency between countries regarding the most appropriate post-retirement solution. Additionally, a disconnect is apparent between what retirees need and want in post-retirement. Successful post-retirement solutions will inevitably blend investment and insurance components in a balanced manner. With lengthening life expectancies, research supports strategies that blend a growth and income account-based approach for the first 15–20 years after retirement with longevity protection in later life.